2004
DOI: 10.1002/ajmg.a.30077
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of two small chromosome 8 derived supernumerary mosaic markers

Abstract: Two small supernumerary mosaic marker chromosomes (SMC) were identified by conventional cytogenetics, one prenatally, the other postnatally. Fluorescence in situ hybridization (FISH) techniques, including 24-color FISH, were applied to identify both SMCs and better characterize their constitution. Patient 1: a 29 year-old man, whose wife had a spontaneous abortion, was found to have a small ring of the pericentromeric region of chromosome 8 (47,XY,+r(8)(p11q11)/46,XY). Patient 2: a 37 year-old woman had amnioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Finally, the slides were counterstained with DAPI. Image acquisition was performed with Isis/mFISH (MetaSystems) (Herry et al, 2004;Douet-Guilbert et al, 2007).…”
Section: Molecular Cytogenetics Lsi Igh/ccnd1 Dual Color Probe the mentioning
confidence: 99%
“…Finally, the slides were counterstained with DAPI. Image acquisition was performed with Isis/mFISH (MetaSystems) (Herry et al, 2004;Douet-Guilbert et al, 2007).…”
Section: Molecular Cytogenetics Lsi Igh/ccnd1 Dual Color Probe the mentioning
confidence: 99%
“…Starke et al [1999] and Engelen et al [2003] summarized 15 and 18 patients, respectively, with supernumerary der(8) and a couple of single cases are described in the literature. Depending on the mosaic status and the size of the supernumerary der(8), the phenotype varied from normal [Nietzel et al, 2001; Liehr et al, 2002; Starke et al, 2003; Gole and Biswas, 2005], or mild intellectual delay [Herry et al, 2004], or dysmorphic features with [Batanian et al, 2000; Anderlid et al, 2001], or without developmental delay [Melnyk and Dewald, 1994; Batanian et al, 2000] up to some clinical features of the trisomy 8 syndrome [Engelen et al, 2003]. In 12 cases, the supernumerary der(8) was of comparable size and band designation to that of the present case: three girls and one boy were phenotypically normal at birth, at the age of 5 months, 9 months, and 2 years, respectively [Starke et al, 1999; Nietzel et al, 2001; Starke et al, 2003; Gole and Biswas, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…Barber et al [1999] have reported that constitutional euchromatic variants in chromosomes 8, 9, 15, and 16 were related with possible amplification of sequences dispersed between pericentromeric and telomeric loci over recent evolutionary time, as a continuum of genomic flux affecting regions where heterochromatin and euchromatin may be interposed. So far, only one clinical case has been reported in the literature, a 29‐year‐old‐male exhibiting a small ring 8p11‐q11 characterized by R‐band, 24‐color FISH, WCP 8, and YAC 959A4 from 8p11 showed mild mental delay but no dysmorphic features, and his wife had a spontaneous abortion [Herry et al, 2004]. Recurrence of spontaneous abortions reported in the present study could be explained by an increased number of sexual and autosomal aneuploidies detected in spermatozoa and testicular biopsy in this patient using FISH (data not shown).…”
Section: Discussionmentioning
confidence: 99%